Penatalaksaan Fisioterapi Pada Kasus Bronchitis Chronic Di RSKP Respira Yogyakarta - Rahmawati, Tiara; , Yulisna Mutia Sari, SSt.FT.,MSc (GRS) (2016)
Background; Chronic Bronchitis is an inflammation of the bronchi caused by irritants or infection, characterized by productive cough and excessive mucus production every day for three months a year in the period of 2 years. Objective; To investigate the implementation of physiotherapy in bronchitis chronic for reducing breathlessness, improving the thorax expansion, reducing sputum, improve PEFR (Peak Expiratory Flow Rate) and reduce tenderness using modalities ACBT (Active Cycle Breathing Technique), nebulizer, infra red and massage. Results; After treatment for 6 times, showed the degree of breathlessness T1: 5 to T6: 2, margin thorax expansion from the axilla in T1: 2 cm into T6: 3 cm, of intercostalis IV on T1: 3 cm into T6: 4 cm, of procesus xypoideus at T1: 2 cm into T6: 3 cm. the results of PEFR on T1: 150 L / min into T6: 215 L / min. results of tenderness in T1: 5.7 cm to T6: 3.5 cm. T1 layout results sputum: sputum is located on top of the left lung lobe and the anterior part of the lower lobe of the right lung and the posterior section T6: sputum layout is still the same as in T1 but the sound produced ronchi diminishing and virtually disappeared. Conclusion; ACBT, nebulizer, infra red and massage can reduce breathlessness, increase thorax expansion, increasing PEFR, reducing sputum and reduce tenderness in patients with chronic bronchitis. Keyword; Chronic Bronchitis, ACBT (Active Cycle Breathing Technique), infra red, nebulizer, massage and PEFR (Peak Expiratory Flow Rate).